Intercellular Communication in Tumor Biology: A Role for Mitochondrial Transfer - Herst, Patries M.; Dawson, Rebecca H.; Berridge, Michael V. (Frontiers in Oncology, 2018)
Intercellular communication between cancer cells and other cells in the tumor microenvironment plays a defining role in tumor development. Tumors contain infiltrates of stromal cells and immune cells that can either promote or inhibit tumor growth, depending on the cytokine/chemokine milieu of the tumor microenvironment and their effect on cell activation status. Recent research has shown that stromal cells can also affect tumor growth through the donation of mitochondria to respiration-deficient tumor cells, restoring normal respiration. Nuclear and mitochondrial DNA mutations affecting mitochondrial respiration lead to some level of respiratory incompetence, forcing cells to generate more energy by glycolysis. Highly glycolytic cancer cells tend to be very aggressive and invasive with poor patient prognosis. However, purely glycolytic cancer cells devoid of mitochondrial DNA cannot form tumors unless they acquire mitochondrial DNA from adjacent cells. This perspective article will address this apparent conundrum of highly glycolytic cells and cover aspects of intercellular communication between tumor cells and cells of the microenvironment with particular emphasis on intercellular mitochondrial transfer.